(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
In the article the features of the advertising text on its structure and functions. Perlocutionary considered, pragmatic effect statements. Analyzed psycholinguistic factors influence expressed by means of syntactic level of language.